2013
DOI: 10.1007/s11065-013-9224-7
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review: Are Overweight and Obese Individuals Impaired on Behavioural Tasks of Executive Functioning?

Abstract: This review was aimed at systematically investigating the evidence suggesting that obese individuals demonstrate impaired performance on behavioural tasks examining executive functioning abilities. A systematic review of literature was carried out by searching five separate databases (PsycINFO, MEDLINE, EMBASE, CINAHL and PubMed) and a hand search of relevant journals. Twenty-one empirical papers were identified from the search criteria and the results were considered in relation to different executive functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
195
1
5

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(206 citation statements)
references
References 42 publications
5
195
1
5
Order By: Relevance
“…Studies that used the IGT found consistent evidence for impaired decision-making under uncertainty, evident in relatively more disadvantageous choices, in overweight and obese as compared to normal-weight adults [e.g., [12,13]]. Likewise, obese and overweight children and adolescents show inferior executive functioning than do their normal-weight peers [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies that used the IGT found consistent evidence for impaired decision-making under uncertainty, evident in relatively more disadvantageous choices, in overweight and obese as compared to normal-weight adults [e.g., [12,13]]. Likewise, obese and overweight children and adolescents show inferior executive functioning than do their normal-weight peers [7].…”
Section: Introductionmentioning
confidence: 99%
“…Although these findings might suggest otherwise, only few studies on weight-group differences in the IGT have taken gender into account. In fact, most of the studies included only female participants or analyzed women and men together [12]. Two studies that compared men and women yielded inconsistent results, indicating that, on one hand, obese women but not obese men show a larger preference than normal-weight controls for high immediate reward and insensitivity to rare but high losses [8].…”
Section: Introductionmentioning
confidence: 99%
“…Impulsiveness has everything to do with not having the ability to inhibit urges towards stimuli and not knowing how to make the right choices. Earlier studies show that many people suffering from obesity have difficulties in decision making, where they often base their decision on what first comes to mind instead of formulating a balance between the pros and cons (Fitzpatrick, Gilbert & Serpell, 2013). Decision making is an important factor in inhibitory control and is essential in making rational choices which would provide the most positive long term outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Decision making is an important factor in inhibitory control and is essential in making rational choices which would provide the most positive long term outcomes. For people suffering from obesity, a lack in decision making and impulsive behavior are specifically related to food and food related stimuli (Fitzpatrick et al, 2013). A number of studies have focused on the underlying mechanisms that lead to this impulsive behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 80% of older adults (+65years) have at least one of the above mentioned chronic diseases, and 50% have at least two chronic disease (1). Along with other organs, brain is also affected with aging and high calorie intake as Fitzpatrik and colleagues suggested in a review article that obese people have problems on decision-making, planning and solving skill, with fewer difficulties on the tasks of verbal fluency, learning and memory (2). In contrast, a reduction of calorie intake without malnutrition called "calorie restriction" (CR) has a wide range of benefits.…”
mentioning
confidence: 99%